The influence of leadership, discipline, and work motivation on organizational culture with implications for employee performance at the food security, crop production, and horticulture office of North Sumatra Province - Batu, Mega Veronika Lumban; Ginting, Rasinta Ria; Romy, Elly (Priviet Social Sciences Journal, 2024)
The purpose of this study is to examine the relationship between leadership, discipline, and employee motivation at the North Sumatra Provincial Office of Food Security, Food Crops, and Horticulture, as well as their performance in relation to organizational culture. A total of eighty-two employees from the UPTD SBPTH unit of the North Sumatra Provincial Office of Food Security, Food Crops, and Horticulture participated in this study. The participants were randomly selected. Data collection employed a combination of primary data obtained through questionnaires and secondary data gathered from documentary analysis. The study adopted a quantitative approach, and the data were analyzed using SPSS version 25, specifically employing t-tests and the coefficient of determination (R²). The findings of the study indicate that leadership, discipline, motivation, organizational culture, and employee performance are all significantly interrelated. The proposed research model elucidates employee performance at the North Sumatra Provincial Office of Food Security, Food Crops, and Horticulture through the variables of leadership, discipline, motivation, and organizational culture.